The Effects of Sexual Frustration on Academic Performance among Young Adults - Adya M Sidharth; Christina Tony (International Journal of Indian Psychȯlogy, 2022)
The present study explores the interconnection between sexual frustration, gender differences and academic performance among young adults. This is a quantitative study and is administered to 62 participants (31 males and 31 females). Convenient sampling technique was used to draw the samples from the population. Instruments such as Arizona Sexual Experience Scale and Academic Performance Scale were used for the collection of data. Karl Pearson Correlation and t- test were used for the analysis of data. The result showed that there is significant difference in sexual frustration among Males and Females also sexual frustration is more in Females than in Males. The current study reveals that Negative Correlation exists between Sexual Frustration and Academic Performance.